A conceptual framework of brand image on customer-based brand equity in the hospitality industry at Bangladesh: Tourism management and advertisement as moderators - Wasib, Latif; Md. Aminul, Islam; Mahadzirah, Mohamad; Md. Abul Hossain, Sikder; Iftekhar, Ahmed (2015)
: In this study, the conceptual framework of brand image is a combination of antecedents and moderators that create differential effects to customer response on customer-based brand equity in the hospitality industry at Bangladesh. By constructing a conceptual framework of brand image, hotels will build a competitive advantage in the hospitality industry that will increase their overall image with long-term sustainability at Bangladesh. Indeed, recent trends in hospitality industry have changed tremendously, and study of a conceptual framework of brand image in the hospitality industry at Bangladesh is increasingly becoming considerable to keep pace with this change. In this conceptual paper, we have summarized the literatures on currently prevailing concepts and approaches on brand image that will allow us to identify the conceptual framework of brand image, and therefore will facilitate hotels to enhance their marketing efficiency and effectiveness at Bangladesh. In this framework, we discussed a case study in Bangladesh, and in light of the findings of this case study we put forward the notion that the conceptual framework of brand image need to be associated with activities of branded hotels at Bangladesh.